Cerebral blood flow based on 3D-ASL technology in the early detection of mild cognitive impairment in type 2 diabetic patients: a pilot study - Hou, Tingzhou; Wang, Yijie; Xu, Hanwen; Shu, Zhenyu; He, Xiaodong; Wu, Xiaohong (Frontiers in Endocrinology, 2025)
ContextType 2 diabetes mellitus (T2DM) significantly increases the risk of mild cognitive impairment (MCI), and earlier recognition is crucial for timely intervention and improving patients’ quality of life.ObjectiveThe aim of this study was to characterize changes in cerebral white matter hyperintensities (WMH) and cerebral blood flow (CBF) based on 3D-arterial spin labeling (3D-ASL) measurements in T2DM with MCI, and to assess their potential as markers for early prediction of MCI.MethodsThis study included 30 T2DM patients stratified into T2DM-MCI and T2DM-nMCI groups using MMSE/MoCA. MRI assessed cerebral WMH volume (T2-FLAIR) and regional CBF (3D-ASL) in temporal, parietal, occipital, and hippocampal areas. Group differences in WMH/CBF were analyzed, ROC evaluated CBF’s diagnostic efficacy for MCI, and CBF-cognition correlations were assessed via Spearman’s analysis.ResultsCranial MRI analysis shows that there were no significant differences between the two groups in terms of total cerebral WMH volume and regional volume (P>0.05). CBF in the temporal, parietal, occipital, and hippocampal regions was significantly lower in the T2DM-MCI group than in the T2DM-nMCI group (P<0.05). ROC analysis revealed that CBF in the hippocampus had the highest diagnostic efficacy (AUC = 0.813, optimal cutoff value of 41.165 ml/(100 g·min), sensitivity 73.3%, specificity 80.0%). Spearman’s correlation analysis showed that CBF in the temporal, parietal, occipital, and hippocampal regions was significantly and positively correlated with MoCA scores (P < 0.05), with temporal and parietal CBF also significantly and positively correlated with MMSE scores (P < 0.05).ConclusionsCBF, based on 3D-ASL measurements, especially in the hippocampus, is a promising functional marker for identifying MCI in patients with T2DM.